Multiple Access Schemes for 6G Enabled NTN-Assisted IoT Technologies: Recent Developments, Prospects and Challenges - Shah, A. F. M. Shahen; Karabulut, Muhammet Ali; Rabie, Khaled (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
The transition from 5G to 6G will result in an explosion of Internet of Things (IoT) devices that provide pervasive and constant connection across all spheres of human activities. In this regard, non-terrestrial networks (NTNs) will play a crucial role in supporting and supplementing terrestrial systems in order to cope with such a vast number of IoT devices and to fulfill the massive capacity needs of the most sophisticated of them. This study investigates the implication of several multiple access techniques for 6G enabled NTN-assisted IoT technologies. First, general architecture of NTN, NTN-assisted IoT technologies, and key features and challenges of NTNs are presented. Then, different types of multiple access schemes are discussed and compared in the context of NTN-assisted IoT systems. Simulation results are presented and important performance parameters such as energy efficiency and spectrum efficiency are examined for the discussed multiple access schemes. Furthermore, challenges and future research directions are discussed.
Keywords: 6G mobile communication; Satellites; 5G mobile communication; Simulation; Boosting; Explosions; Energy efficiency; Computer Science; Engineering; Telecommunications